Smuggling as a Form of Illegal Evasion of Public Revenue (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
In modern societies today complete legal descriptions of criminal offenses, related to the illegal audit of public revenues usually appear as tax evasion, customs fraud and smuggling. It will be the crime of smuggling phenomenon, as one of the forms of illegal evasion of public revenue, specifically is criminal offense, which is mainly related to the illegal transfer of goods, across the customs line, avoiding customs controls. Smuggle can also be people, weapons, medicines, drugs, information and data, artwork, plants, animals, software, copyrights, etc. The paper points to the smuggling of goods and services as the growing phenomenon of classical and organized crime. The aim of this work is that through the observation of case studies of the phenomenon of smuggling luxury goods, point to one of the modus operandi forms of smuggling luxury goods from EU countries, on the territory of Bosnia and Herzegovina. The paper also presents the results of scientific tests and research, legal and regulatory restrictions in Bosnia and Herzegovina, to combat illegal evasion of public revenue.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.